Identifying the psychological State of female Volleyball team in the college of physical Education – University of Baghdad - Hammad Jumaili, Saad; Yasser al-Obeidi, Nedaa; khadr Behnam, Baidaa (Journal of Physical Education, 2012)
The research aims to identify the causes that lead to fear and anxiety in the practices of the game of volleyball in the Faculty of Physical Education / University of Baghdad, and also to recognize cases or situations psychological occurring in female practices for volleyball game team in the Faculty of Physical Education / University of Baghdad, has been formed The research sample of players elected Faculty of Physical Education posts in the league primarily on stadium Physical Education College / University of Baghdad for season 2012 and of team coach college team Tdriciat college’s (20) player, was selected way intentional, were excluded (5) players for lack of commitment to training The remainder (15) player participating in the tournament. It was concluded researcher most important results is that most of the respondents and of their number (7) student at a rate of 46.7% said they felt no confidence themselves before the game but during the game, the self-confidence gradually increased, as well as concluded researcher that (6) student and 40% occur have sometimes quickly emotion unlike the students of their number (5) students and the percentage of 33.3% that they quickly feel emotion. The researcher recommended the most important recommendations including: a great deal of psychological tests by specialists on the players and the players volleyball because of its importance in the games, and a lot of friendlies and competitions and tournaments for the purpose of raising the efficiency of psychological players volleyball and get rid of fear and anxiety .